The Relationship Between Parents' Support And Economic Status With Student's Interest In Entrepreneurship Family Welfare Education Program Padang Negeri University - Kurniawati, Windy; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research was motivated by a decrease in the interest of students of the Family Walfare Education Study Program to continue the bisiness they had founded. This study aims to: 1) describe the support of parents of PKK students regarding entrepreneurship; 2) describe the economic status of the parents of PKK Study Program students; 3) describe the interest in entrepreneurship for PKK Study Program students; 4) analyze the relationship between parental support and interest in entrepreneurship for PKK Study Program students; 5) analyzing the relationship between the economic status of parents and the interest in entrepreneurship for PKK Study Program students; 6) analyze the relationship between the support and economic status of parents with the interest in entrepreneurship for students of the PKK Study Program. This type of research is quantitative with a correlational approach. The research population was 333 students of the Family Welfare Education Study Program class of 2018-2019. The sampling technique used was proportional random sampling with a total sample of 77 people. Data was collected through a questionnaire in the form of a google form which was arranged based on a Likert scale, which was then tested for the validity and reliability of the problem items. Data were analyzed by descriptive analysis and correlation. The results showed that parental support related to entrepreneurship was in the high category is 23 people (30%). Parents' economic status is in very low category is 49 people (64%). Students' interest in entrepreneurship is in the high category is 30 people (39%). The results of the correlation test between parental support and interest in entrepreneurship show that there is a significant relationship with a value of 0.000 <0.005. The results of the correlation test between the variables of parents' economic status and interest in entrepreneurship, namely that there is no significant relationship with a value of 0.656> 0.005. Finish be concluded that there is a significant relationship between the support and economic status of parents together with the interest in entrepreneurship of students of the Family Welfare Education Study Program with a significant value of 0.000 <0.005.